Shopping Malls as Urban Third Places for Generation Y and Z in Bali - Ida Ayu Shanty Pradnya Paramitha; Ardina Susanti (Program Studi Arsitektur, Fakultas Teknik dan Perencanaan, Universitas Warmadewa, 2025)
This study examines the role of shopping malls as urban third places for Generations Y and Z in Bali, a rapidly developing and tourism-oriented region where traditional communal spaces increasingly coexist with modern commercial environments. Using a mixed-method approach that integrates perceptual surveys (n = 119), field observations, spatial documentation, and correlation analysis, the research investigates how malls support contemporary sociability, cultural expression, and digitally mediated interaction. Findings show that malls are the most frequently visited indoor third places among young residents, valued for their accessibility, climate-controlled comfort, and diverse amenities. Correspondence analysis reveals four dominant activities shared by both generations: casual conversation, eating and drinking, exploring places, and people-watching, while Generation Z demonstrates a stronger inclination toward solitary, observational, and digital activities. Case studies of Living World Mall and Mal Bali Galeria illustrate two distinct spatial typologies: an experiential, flexible, youth-oriented environment and a community-oriented, familiarity-based environment. Key spatial factors such as seating availability, shading, façade permeability, greenery, and thermal comfort significantly influence users’ third place perceptions. Overall, the study shows that malls in Bali function as hybrid social infrastructures that redefine Oldenburg’s third place concept, highlighting the interplay between commercial design and generational behaviors in shaping contemporary public life.